2014
DOI: 10.1136/vr.102634
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium species nasal carriage in pigs and their farmers in Bavaria, Germany: implications for public health

Abstract: Reports on cases of human diphtheria caused by toxigenic Corynebacterium ulcerans that were linked to occupational swine contact as well as isolation of C ulcerans from wild boars have suggested that pigs might serve as reservoir for human infections. Therefore, a prevalence study on Corynebacterium species nasal carriage in pigs and their farmers was performed between August 1 and December 31, 2009, in 41 swine farms from Bavaria, Germany. All 411 asymptomatic pigs and 29 of 30 healthy farmers were colonised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Companion animals such as dogs [ 5 – 9 ] and cats [ 10 13 ], as well as pigs [ 14 , 15 ] have been shown to harbor C. ulcerans and may play a role as sources of infection for human. However, whether cats or dogs are the natural hosts for the bacterium is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Companion animals such as dogs [ 5 – 9 ] and cats [ 10 13 ], as well as pigs [ 14 , 15 ] have been shown to harbor C. ulcerans and may play a role as sources of infection for human. However, whether cats or dogs are the natural hosts for the bacterium is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some of these have been associated with respiratory disease, as exemplified for porcine astrovirus type 4 and Corynebacterium , which is a known opportunistic pathogen that causes purulent infections (e.g., Corynebacterium pyogenes ) ( 52 , 53 ). The latter is also considered to be important from the One Health perspective, as different cases of human infections after contact with pigs have been reported ( 54 ). Hence, this highlights the potential added value of metagenomics-driven diagnostics for both animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Several prevalence studies (of between 60 and 13,310 animals, Table 1) have indicated that the bacteria may be carried by 0.4%–29% of monkeys in closed breeding colonies (Hirai‐Yuki et al., 2013; Panaitescu et al., 1977), 0.07%–7.2% of dogs in shelters, local government custody, or veterinary hospitals (Museux et al., 2023; Abbott et al., 2020; Dias et al., 2010; Katsukawa et al., 2012), and 6.25% of cats in veterinary hospitals (Abbott et al., 2020). One prevalence study in farm pigs found many Corynebacterium species, but not C. ulcerans (Boschert et al., 2014).…”
Section: Introductionmentioning
confidence: 99%